Mysterious glowing mammals : an unexpected discovery sparks a scientific investigation - Parrott-Ryan, Maria (Millbrook Press, an imprint of Lerner Publishing Group, Inc., 2024)
"One night a scientist discovered something surprising in his own backyard : a flying squirrel that glowed bright pink! Follow along on an investigation into flying squirrels -- and other mammals -- that glow when exposed to ultraviolet light"--